Influence of Different Information Presentation Formats on Consumer Acceptability: The Case of Goat Milk Presented as Obtained from Different Rearing Systems. Issue 2 (27th March 2015) - Musto, M.; Cardinale, D.; Lucia, P.; Faraone, D.
Abstract The present study aimed to evaluate whether information about the main aspects related to milk production practices adopted in the two major systems of small ruminant farming (i.e., intensive and semi‐extensive rearing systems) can affect consumer acceptability of two different types of goat milk: semi‐skimmed and whole milk. Four milk‐information combinations were evaluated in two experiments, which differed for the information presentation formats (i.e., textual description versus video with narration). Information about semi‐extensive rearing system had a high positive effect on milk liking, especially in video‐with‐narration condition. Moreover, this information presentation format generated higher hedonic expectations for milk presented as obtained from intensive rearing system than did textual description only. We conclude that information about some farming practices related to milk production may be important for helping consumers to make informed food choices, especially when conveying it by a video‐with‐narration format. Practical Applications The disclosure of information about livestock production practices is important for shortening the distance between those who produce food and their consumers. Illustrating such information may help consumers to understand how food is produced and, hence, to build their trust in food production. Our results show that video with narration seems to be an effective presentation format for conveying such information. In a purchase situation, this may be achieved via the Internet, for instance, by voluntarily printing a matrix barcode on a food label. When scanned by a smartphone, the barcode can direct the smartphone to display a video, text or other information, which may help consumers to make more informed food choices. The adoption of this strategy may contribute to differentiate animal products from farms aimed at boosting their transparency in the global market of food.